Conflicts among Primary School Educators: Causes, Effects and Management styles - Τσεκούρα, Ελένη (Education Sciences, 2024)
Conflict among educators constitutes a daily phenomenon within educational organizations yet, according to modern theories, its successful management along with sustaining conflict at an optimum level could benefit them. This study attempted to investigate the causes of conflict among primary school educators, the methods applied to deal with a potential conflict as well as the effects, both positive and negative, that conflicts bring about at a school unit level. The findings of this research indicate that educators can successfully identify past rather than present conflict. The primary cause of conflict seems to originate from personal differences. Primary school teachers tend to apply the method of cooperation to resolve conflict among them, women significantly choose the method of avoidance while teachers with limited working experience notably distance themselves from the use of the dominance method. As for the consequences that conflict entails for primary schools, the majority of teachers advocate that negative ones outweigh the positive ones.